Poor PLS of Security Sector Reform and Its Impacts on Human Rights and Civil-Military Relations in Indonesia - Poltak Partogi Nainggolan; Riris Katharina (Journal of Southeast Asian Human Rights, 2020)
As emerging democracy, Indonesia is facing a formidable challenge from its Parliament whose capacity in conducting Post-Legislative Scrutiny is weak; this could prevent the country from fulfilling democratic consolidation. The country’s failure in fulfilling its democratic consolidation two decades after Soeharto’s resignation can bring it back to the authoritarian era as it has experienced only two years after the first 1955 democratic election until 1998. Applying an empirical research by directly observing PLS in the Indonesian parliament and using a qualitative method of analysis, this essay discussed the causes and repercussions of the parliament’s poor capability, which have brought the country into current setback, facing resistances from the old establishment that has made the military unable to continue reform and to change its political culture. Therefore, the Indonesian military still wants to involve in civilian affairs and businesses by making a more flexible interpretation of Military Operations Other Than War, on the one side. While, on the other, TNI’s existing culture of violence has led it to many alleged cases of gross human rights violations which could not be prosecuted until recently. In fact, Indonesian Members of Parliament’s poor capability and DPR’s weak supporting system give more complexity to the country in its struggle and success to be the third biggest democracy in the world.